2011
DOI: 10.1186/1476-9255-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation alters airway inflammation and airway hyperresponsiveness to a common allergen

Abstract: BackgroundZinc supplementation can modulate immunity through inhibition of NF-κB, a transcription factor that controls many immune response genes. Thus, we sought to examine the mechanism by which zinc supplementation tempers the response to a common allergen and determine its effect on allergic airway inflammation.MethodsMice were injected with zinc gluconate prior to German cockroach (GC) feces (frass) exposure and airway inflammation was assessed. Primary bone marrow-derived neutrophils and DMSO-differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…El-Kholy et al reported that adequate dietary intake of zinc and zinc supplementation might decrease the severity of asthmatic attacks (26). Animal studies also demonstrated that zinc supplements reduced inflammatory and airway hyper-responsiveness (27). Prasad et al showed that zinc decreased oxidative stress and nuclear transcription factor NF-κB activation in isolated mononuclear cells via induction of zinc finger protein A20 (28).…”
Section: Spirometry Parametersmentioning
confidence: 99%
“…El-Kholy et al reported that adequate dietary intake of zinc and zinc supplementation might decrease the severity of asthmatic attacks (26). Animal studies also demonstrated that zinc supplements reduced inflammatory and airway hyper-responsiveness (27). Prasad et al showed that zinc decreased oxidative stress and nuclear transcription factor NF-κB activation in isolated mononuclear cells via induction of zinc finger protein A20 (28).…”
Section: Spirometry Parametersmentioning
confidence: 99%
“…There are several studies that have examined the influence of zinc on A20-mediated NF-κB inhibition [39][40][41].Moreover, zinc inhibits NF-κB activation in the DNA nuclear binding levels by increasing the expression of peroxisome proliferator-activated receptor α (PPAR-α), which is a mediator for lipoprotein metabolism, inflammation, and glucose homeostasis. PPAR-α increase leads to the down-regulation of inflammatory cytokines and adhesion molecule [42].…”
Section: A Nf-κb and Other Signalling Pathwaymentioning
confidence: 99%
“…[26][27][28][29] It is therefore interesting to note that there was no major difference in the development of neovascularization between the treatment groups in our study. Further, it is known that patients with RVO have a unique array of vitreous proteins 30,31 , and that ischemic CRVO is associated with increased concentrations of a distinct set of these vitreous proteins. 26 It therefore may be possible that ranibizumab reduced the development of ischemia in our study by altering the angiogenic balance, however, further research is needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%